GERENCIAMENTO DE RISCO DE MEDICAMENTOS POTENCIALMENTE PERIGOSOS PELA ENFERMAGEM EM UNIDADES DE TERAPIA INTENSIVA - Patricia Trindade Benites (2021)
The consequences of errors with potentially dangerous medications (MPP) confirm the importance of efficient management regarding the prescription, dispensation and administration of these drugs. Additionally, the handling of drug therapy in intensive care units (ICU) is quite complex due to the numerous drugs used. The objective was to analyze the risk management of MPP by nursing in the ICU. This is a cross-sectional, analytical study with a quantitative approach, carried out with nurses who worked in 11 ICUs in two hospitals, using a validated and adapted instrument. The research protocol for this study was approved by the Research Ethics Committee (opinion No. 4,228,156). Data were collected between August and September 2020, at the professionals' workplace. The results showed that most professionals consider that they have an excellent level of knowledge about MPP (83.16%) and have not received training on the topic in the last year (68.4%). None of the MPP was recognized by 100% of the participants as such; eight of the MPP were marked as used by 90% of nurses and technicians. Of these, norepinephrine was the most indicated as used (98.8%) and most marked as MPP (97.6%). Among the drugs frequently used in ICUs and not marked as MPP, the following stand out: Sodium chloride 20%, Tramadol, Lidocaine, Potassium phosphate, total parenteral nutrition (TPN), Sterile water, Magnesium sulfate, Potassium chloride and Peritoneal dialysis / hemodialysis solutions. Regarding damage prevention measures for the use of MPP, 70.65% of professionals admitted their existence in their work unit. Professionals with a higher level of knowledge about MPP indicated that they use more damage prevention measures (p = 0.035). Only 16% of the professionals indicated that they perform the MPP double check often or always, and the verification of certain drug therapy is always performed by only 63% of the interviewees. Most respondents (70%) reported that they never received training programs on the spot. Regarding the obstacles to management, the most pointed item was the confused / incomplete medical prescription (65%). The results show that there are safety barriers implemented in the ICUs, however, they present weaknesses, such as the failure to double-check the medications and verify certain drug therapy. These facts demonstrate the need for safety barriers to be standardized and incorporated by health teams to promote safe and effective assistance. In addition, the lack of qualification and training of professionals increased the chances of these barriers not being practiced correctly and effectively.